Trademark Registration for OCOP Products Abroad - Van Hai, Tran (VNU Journal of Science: Policy and Management Studies; Vol 41 No 1DO - 10.25073/2588-1116/vnupam.4544, 2025)
According to the Intellectual Property Office of Vietnam (IP Vietnam), all 63 provinces and cities in the country have assessed and ranked OCOP (One Commune One Product) products, with 11,056 products rated three stars or higher. Specifically, 68.9% are three-star products, 29.9% are four-star products, and 42 products have been awarded five stars, while the remainder is considered potential five-star products. [1] Under Decision No. 148/QĐ-TTg, issued by the Prime Minister on February 23, 2023, which establishes the criteria and regulations for evaluating and ranking OCOP products, any product seeking a four-star or higher rating must be granted a trademark registration certificate. However, Vietnamese localities and businesses are currently facing difficulties in registering trademark protection for OCOP products abroad. To address these difficulties, the Central Coordination Office for New Rural Development has proposed that the IP Vietnam issue a guideline on registering trademarks for OCOP products in Northeast Asia (primarily China), the United States, the EU, Australia, New Zealand, Singapore, India, Laos, Cambodia, and Myanmar. [1] This article examines intellectual property laws related to trademarks containing foreign geographical elements in certain countries and proposes solutions for trademark registration in countries that import Vietnam’s OCOP products. .